Cardiac rupture caused by Staphylococcus aureus septicaemia and pericarditis: an incidental finding. Issue 3 (1st March 2001) - Osula, S; Lowe, R; Perry, R A
Abstract : A 35 year old woman with a long history of intravenous drug abuse presented to a local hospital with severe anaemia, fever, raised markers of inflammation, and positive blood cultures for Staphylococcus aureus . She responded to treatment with antibiotics with improvement in her symptoms and markers of inflammation. Four weeks later a "routine" echocardiogram showed a rupture of her left ventricular apex and a large pseudoaneurysm. There had been no deterioration in her symptoms or haemodynamic status to herald this new development. It was successfully repaired surgically and the patient made a good recovery.